Analisis Kedalaman Potensi Akuifer Air Tanah dengan Pemodelan Distribusi Tahanan Jenis secara Inversi 2-D Desa Kompas Raya, Nanga Pinoh, Melawi, Kalimantan Barat - Karunianto, Adhika Junara (BRIN Publishing, 2013)
Geophysical investigation by geoelectrical resistivity method have been done at Kompas Raya Village, Pinoh, Melawi, West Kalimantan Province. Kompas Raya Village is an area that is always a lack of water in the dry season, so the villagers are always difficult to get clean water to meet their daily needs. This study aimed to look resistivity distribution both laterally and vertically in two dimensions. The data distribution of resistivity can be used as a basis to determine the potential aquifers in the area of research. The measurement method of sounding resistivity is performed by Schlumberger Configuration. The numbers of measuring points are 30 points soundings which are divided into six survey paths each where each survey path is contained five measuring points. In this study, resistivity data processing is performed using 2D inversion modeling techniques based on data resistivity sounding. The results obtained from this study is the presence of two layers of relatively low resistivity that is each less than 30 Ohm.m and 20 Ohm.m. The first layer is interpreted as a shallow aquifer (aquifer-1) with the depth of about 20 m to 30 m, while the second layer is interpreted as the aquifer (aquifer-2) with the depth of about 90 m to 100 m.